Islam and politics in Malaysia: the realisation of Islam as a state religion in Sabah - Syed Hamid, Sharifah Sara Hasliza; Akhmetova, Elmira (IIUM Press, International Islamic University Malaysia, 2019)
This paper analyses the process of independence in Sabah and the consequent Islamisation of its population, which caused the amendment of the State Constitution in 1973. The first part of the paper states that the unification of Sabah with Malaya into the Federation of Malaysia guaranteed its independence from the British colonial rule as well as saved it from the communist threat. The next part of the paper suggests that the Islamisation activities were highly associated with the political needs of the government where the Muslim political leaders strived for increasing the number of their supporters in order to maintain their seats as the ruling government in Sabah. Thus, the paper finds the strong relationship between Islam and politics in modern nation-states, and concludes that the rapid growth of the number of Muslims in Sabah later created the quality problem as their religious education was not seen as the priority by the ruling government.